Recurrent Metatarsal Fractures in Postmenopausal Woman With Low Serum Alkaline Phosphatase: A Rare Diagnosis Not to Miss - Umair Iqbal MD; Hafsa Anwar MBBS; Ahmad Chaudhary MD; Madiha Alvi MD; Amy Freeth MD (SAGE Publishing, 2017)
Hypophosphatasia (HPP) is a rare inborn error of metabolism due to a loss-of-function mutation in the gene for tissue nonspecific isoenzyme of alkaline phosphatase (ALP) that results in low levels of ALP. The clinical presentation of HPP is variable and in adults can easily be misdiagnosed as other forms of osteomalacia. We present a case of a 53-year-old Caucasian female who was evaluated for recurrent metatarsal fractures. She reported her first metatarsal fracture at age 21, and since then had at least 8 more metatarsal fractures over her lifetime, most without injury other than weight bearing. She reported history of gait disturbance as a child and dental issues (spacing and loosening). Laboratory tests showed normal serum calcium, phosphorus, and parathyroid hormone, but low serum ALP <20 IU/L and elevated N-telopeptide. Foot X-ray showed several healed and nonhealed metatarsal fractures, and bone densitometry revealed osteopenia. She was treated with calcium and vitamin D. A year later she had a new metatarsal fracture and a nontraumatic pelvic fracture. Teriparatide therapy was attempted but not tolerated. Due to suspicion of HPP vitamin B 6 levels were checked and found to be elevated at 263 µg/L. Given her clinical presentation and low ALP levels with elevated vitamin B 6 , the diagnosis of HPP was made. Clinicians should be attentive to a history of recurrent low trauma fractures, premature loss of deciduous teeth, and persistently low serum ALP to suspect this diagnosis. Early case detection with the availability of recent Food and Drug Administration-approved asfotase alfa may avoid years of undiagnosed morbidity.